2016
DOI: 10.1016/j.sdentj.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived halitosis and related factors among adults residing in Riyadh, Saudi Arabia. A cross sectional study

Abstract: The prevalence of self-perceived halitosis among the population in Riyadh is within the range reported in other countries. Self-perceived halitosis is related to gender, inadequate oral hygiene practices and cigarettes and shisha smoking however, it is not related to age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 23 publications
(42 reference statements)
8
47
3
1
Order By: Relevance
“…Oral hygiene habits such as toothbrushing and dental flossing were also associated with self‐reported halitosis in the present study (model 1 and model 3). This is in accordance with previous studies (AlSadhan, ; Lopes et al, ) that also reported an association with tongue cleaning. However, Milanesi et al () demonstrated that any mouthwash use, frequency of toothbrushing, interproximal cleaning and tongue cleaning were not retained in the final model for self‐reported halitosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Oral hygiene habits such as toothbrushing and dental flossing were also associated with self‐reported halitosis in the present study (model 1 and model 3). This is in accordance with previous studies (AlSadhan, ; Lopes et al, ) that also reported an association with tongue cleaning. However, Milanesi et al () demonstrated that any mouthwash use, frequency of toothbrushing, interproximal cleaning and tongue cleaning were not retained in the final model for self‐reported halitosis.…”
Section: Discussionsupporting
confidence: 94%
“…Predictors associated with self‐reported halitosis also varied among studies, but included some demographic data such as age, gender, educational level and family income (AlSadhan, ; Milanesi et al, ; Youngnak‐Piboonratanakit & Vachirarojpisan, ). In the present study, educational level and family income were retained in the final model (model 1) for the self‐reported measure 1 and age and gender were retained in the final model (model 3) for the self‐reported measure 3.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Recently, AlSadhan reported the presence of self-perceived halitosis in 22.8% of study participants (aged 17–65 years) in Saudi Arabia. [ 15 ] The prevalence of self-reported halitosis was 28.3% in Turkish individuals aged >55 years. [ 16 ] The prevalence rates range from 20% to >50% of world population.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontists should be aware that patients under routine therapy may be affected by inappropriate oral health procedures, which can cause oral malodor, leading to personal discomfort and even social embarrassment. 20,22 The hypothesis formulated was confirmed.…”
Section: Discussionmentioning
confidence: 60%
“…In this investigation, malodor was related to inadequate oral hygiene practices, which is consistent with the findings of other studies; however, those studies did not consider adolescents under orthodontic therapy. 20,21 With regard to the sample's social demographics, although the subjects had middle education, it was deduced that they were not fully aware of oral malodor etiopathogeny and, consequently, its management.…”
Section: Discussionmentioning
confidence: 99%